Remini-Sing: A Feasibility Study of Therapeutic Group Singing to Support Relationship Quality and Wellbeing for Community-Dwelling People Living With Dementia and Their Family Caregivers - Tamplin, Jeanette; Clark, Imogen N.; Lee, Young-Eun C.; Baker, Felicity A. (Frontiers in Medicine, 2018)
Background: Living at home following a diagnosis of dementia can be difficult for both the person living with dementia (PwD) and their family caregivers (FCG). Active group music participation may provide an avenue for emotional release, offer psychosocial support to caregivers and stimulate meaningful interaction between caregivers and loved ones with dementia. Therapeutic music interventions also have the capacity to facilitate reminiscence and social engagement and can help to manage challenging symptoms associated with dementia, such as anxiety, apathy, and agitation. Method: This feasibility study examined the acceptability of a 20-week therapeutic group singing intervention (Remini-Sing) and quantitative research assessments for PwD/FCG dyads living in the community. Quantitative measures for the following outcomes were tested for sensitivity and acceptability: relationship quality (PwD and FCG); life satisfaction, caregiver satisfaction, flourishing, and depression for FCGs; and anxiety, apathy, agitation, and quality of life for PwD. Quantitative assessments were conducted before, during (midway) and after 20 weeks of participation in a therapeutic singing group attended by the PwD and FCG together. The Remini-Sing intervention incorporated vocal warm ups, singing familiar songs, learning new songs, and opportunities for social interaction. Qualitative interviews were conducted with all dyads that completed the intervention. Results: Twelve PWD/FCG dyads were recruited and enrolled in the study. High participation and retention rates indicated that the intervention was received favourably by participants. There were no statistically significant changes on measures from pre to post intervention. However, favourable baseline scores on relationship quality and wellbeing measures were sustained over the 20-week intervention. The testing of these measures for feasibility also revealed that some were too difficult for PwD and thus yielded questionable results, some were potentially less relevant, and there were likely floor and ceiling effects on several of the measures utilized. Conclusions: This study demonstrated good feasibility for a research protocol and therapeutic group singing intervention for community-dwelling PwD and their FCGs. Participant reflections and researcher observations yielded useful information guiding the selection of quantitative outcome measures for future research in this area.